The Use of Technological Tools- Movie Maker and Weblogs to Foster Social Interaction in the Classroom - Suasnavas, Karina (Kronos – The Language Teaching Journal, 2018)
This present work depicts a literature review on how the use of technological tools such as Weblogs and Movie Maker can build social interaction within the classroom; while students implicitly learn English and foster the use of values in the learning process. It also briefly discusses the impact of technology in teaching, and why to use the aforementioned technological tools in class. Examples of tools to create weblogs are provided. Furthermore, this paper suggests two purposeful strategies: Literature Circles and Project Menus that can be used and combined with Weblogs and Movie Maker in order to enhance teachers’ instruction, and to make students develop the language skills in an integrated and interactive way.